Shine a light on papyrus: monitoring the aging process - Florian Bausch; Dickson D. Owusu; Jörg Graf; Thomas Rosenau; Antje Potthast (Heritage Science, 2022)
Abstract The aging behavior of ancient papyri is not entirely understood, although such understanding is crucial for tailored conservation concepts to preserve these precious historical documents for the millennia to come. In a study on accelerated aging, the effect of light on papyrus sheets was studied, and the consequences were monitored by a combination of non-invasive and invasive techniques. Papyrus sheets were aged for two months at 90 °C and 50% relative humidity, with and without the influence of light. Changes at the optical, mechanical, and molecular levels were monitored using CIELAB color measurements, tensile tests, Fourier transform-infrared spectroscopy (FTIR), and size exclusion chromatography—multi angle light scattering (SEC-MALS). Light exposure has severe consequences for the optical and mechanical properties of papyri, reflected by a strong decrease in cellulose chain length and tensile strength. SEC-MALS proved to be the best method to assess the conservation status of papyri due to its clear results and low sample demand. This publication seeks to highlight the effects of light-induced degradation of papyri and to facilitate an understanding of the underlying aging mechanisms, to support in future conservation measures. Graphical Abstract